Pengaruh Penerapan Pengendalian Internal Terhadap Pencegahan Fraud Pengadaan Barang - Hermiyetti Hermiyetti (Jurnal Akuntansi dan Auditing Indonesia, 2010)
The aim of this study is to analyze the effect of internal control applying on procurement fraud prevention. Survey the sum of 23 respondent covering financial directors on the public and private hospital on Bandung city. Data have been collected by questionnaire. The tools of statistic analysis using path analysis. The result of this study indicates that there are effects of internal control applying on procurement fraud prevention. It means that procurement fraud prevention inclined by internal control applying and influenced residue by other factors which not integrated in this study model.Keywords: Internal control, procurement, fraud prevention